Continuous usage intention to e-transaction cards in wholesale markets of agriproducts: Empirical evidence from China - Xuechao Sui; Xianhui Geng (Future Business Journal, 2021)
Generalizing the e-transaction services in wholesale markets of agriproducts is seen as a way for the government in China to enhance its information services capabilities. These services could also facilitate the transactions of traders. We find that traders are reluctant to use e-transaction cards although they have physical access. This paper identifies factors influencing traders' continuous usage intention to e-transaction cards in wholesale markets of agriproducts in China. Data were collected from 204 respondents through a self-administered survey completed by traders and analyzed by structural equation modeling (SEM). The results explore that perceived ease of use (PEOU), perceived usefulness (PU) and perceived privacy security (PPS) directly and positively affect traders' continuous usage intention. It is also demonstrated that both PEOU and perceived transaction security indirectly and positively affect continuous usage intention through PU. This research provides practical guidelines for decision makers to increase traders' intention to e-transaction cards.
Keywords: O33; Q13; Q16; 650; China; Continuous usage intention; E-transaction; Wholesale markets of agriproducts